2017
DOI: 10.1007/s40618-017-0708-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease in women with polycystic ovary syndrome: systematic review and meta-analysis

Abstract: The prevalence of NAFLD is increased in women with PCOS and the presence of NAFLD is associated with high serum androgen levels, in addition to obesity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 55 publications
9
77
1
16
Order By: Relevance
“…Hyperandrogenism measured by FAI was also an independent predictor of NAFLD. Our nding con rms previous data that high FAI correlates with liver disease markers and is a PCOS-speci c feature that further increases the risk of NAFLD (13). Elevated ALT was also an independent predictor of NAFLD on multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Hyperandrogenism measured by FAI was also an independent predictor of NAFLD. Our nding con rms previous data that high FAI correlates with liver disease markers and is a PCOS-speci c feature that further increases the risk of NAFLD (13). Elevated ALT was also an independent predictor of NAFLD on multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
“…These gures are higher than those reported for the general population, where the prevalence of NAFLD is 25.24% (1,28). Previous estimates of NAFLD prevalence among PCOS patients ranged widely, between 5.5% and 73.3% across studies (13). In the present study, we have included a homogeneous population of South Asian women, as both PCOS and NAFLD prevalence vary across ethnicities (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes may explain the increased VTE risk that we observed, beyond high BMI, smoking, and hormone use. Moreover, women with PCOS have also been found to have a higher prevalence of non‐alcoholic fatty liver disease than women without the syndrome . Non‐alcoholic fatty liver disease is associated with increased procoagulant levels, which may also contribute to an increased VTE risk …”
Section: Discussionmentioning
confidence: 99%
“…88 A recent systematic review and meta-analysis of 17 studies has revealed that PCOS patients (n = 2,734) have increased prevalence of NAFLD (OR: 2.54, 95% CI 2.19-2.95) and the presence of NAFLD among them is associated with hyperandrogenism, in addition to IR and adiposity. 89 The prevalence of NAFLD among women with PCOS is estimated to vary from 15% to 55%, whereas amongst the reproductive-aged women with NAFLD, the prevalence of PCOS is as high as 71%. 90 OSA OSA is strongly associated with NAFLD independent of traditional risk factors.…”
Section: Pcosmentioning
confidence: 99%